Driving Towards a Reduction of Domestic Violence in Numan Community, Adamawa State - Falda, Wesley (Corpus Intellectual, 2023)
Abuse intended to control or cause harm to a partner is known as domestic violence. One of the main reasons for gender-based violence is the misuse of authority. Domestic abuse can take many different forms, such as financial, emotional, sexual, or physical. While victims can be of any age or gender, it most frequently affects women between the ages of 18 and 34. The goal of the research was to promote a decrease in domestic violence in Adamawa State's Numan community. Since the study's population was so big, it was limited to domestic abuse survivors who attended Hope Center Numan. From this group, a Simple Random Sampling (SRS) was used to choose a capable responder who would serve as a representative sample for the total population. The study's conclusions showed that the main factor contributing to domestic violence in the community is poverty. Because there are so many unemployed people in the town, alcoholism and a lack of income can occasionally result in domestic violence inside the family. Therefore, it is advised that in order to lessen domestic violence, both men and women should have more influence in the community. To lessen the prevalence of domestic violence in society, the community should be educated on its impacts and ways to prevent it.